Rewrite in simplest terms: (9x+5)-(-2x+10)(9x+5)−(−2x+10)

Question

Rewrite in simplest terms: (9x+5)-(-2x+10)(9x+5)−(−2x+10)

in progress 0
Thanh Hà 3 years 2021-08-06T14:02:58+00:00 1 Answers 10 views 0

Answers ( )

    0
    2021-08-06T14:04:15+00:00

    \implies {\blue {\boxed {\boxed {\purple {\sf {  18 {x}^{2}  - 69x - 55}}}}}}

    \large\mathfrak{{\pmb{\underline{\orange{Step-by-step\:explanation}}{\orange{:}}}}}

     = (9x + 5) - ( - 2 x+ 10)(9x + 5) - ( - 2x + 10)

       = (9x + 5)  + 2x (9x + 5) - 10(9x + 5) - ( - 2x + 10)

     = 9x + 5 + 18 {x}^{2} + 10  x- 90x - 50 + 2x - 10

    Collect the like terms.

     = 18 {x}^{2}   + (9x   + 10x- 90x + 2x) + (5  - 50 - 10)

     = 18 {x}^{2}   + (21x - 90x) +(5 - 60)

     = 18 {x}^{2}  - 69x - 55

    \boxed{    Note:}

    \sf\pink{PEMDAS\: rule.}

    P = Parentheses

    E = Exponents

    M = Multiplication

    D = Division

    A = Addition

    S = Subtraction

    \red{\large\qquad \qquad \underline{ \pmb{{ \mathbb{ \maltese \: \: Mystique35♛}}}}}

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )